Menganalisis Pengaruh Non-Performing Financing (NPF), Kewajiban Penyediaan Modal Minimum (KPMM), dan Financing to Deposit Ratio (FDR) Terhadap Cadangan Kerugian Penurunan Nilai (CKPN) pada Perbankan Syariah di Indonesia - Irawati Irawati; Mutiah Khaira Sihotang (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This research aims to analyze the influence of NPF, KPMM, and FDR on CKPN on sharia banking in Indonesia. Research methods with quantitative methods described in multiple linear regression analysis models. The research population was sourced from the Financial Services Authority through Sharia Banking Statistics. This type of research with secondary data in the form of monthly data from 2017 to 2022 was then progressed with multiple regression analysis so that 72 data were obtained. The technique of nonprobability sampling by purposive sampling. The results of the study are as follows: (1) The estimation model shows an R2 value of 0,73 which represents the value of the coefficient of determination. This means that 73% of the dependent variable variation is able to be explained by the independent variables in this model. The remaining 27% is explained by other causes that are not included in the model; 2) The regression model on the independent variable simultaneously influence the dependent variable, so that the independent variable regression model can be used to predict the dependent variable; and (3) This research results in the output that NPF has an influential and significant effect on CKPN in sharia banking in Indonesia. This research also produced the results that KPMM and FDR have no effect and are not significant on CKPN in sharia banking in Indonesia.